Nitrobenzoxadiazole derivatives of the rat selective toxicant norbormide as fluorescent probes for live cell imaging. (1st April 2022) - Wang, Zifei L.; Li, Freda F.; Quach, Rachelle; Ferrarese, Alessandro; Forgiarini, Alessia; Ferrari, Mauro; D'Amore, Claudio; Bova, Sergio; Orso, Genny; Fusi, Fabio; Saponara, Simona; Hopkins, Brian; et al.
Graphical abstract: Abstract: Norbormide [5-(α-hydroxy-α-2-pyridylbenzyl)-7-(α-2-pyridylbenzylidene)-5-norbornene-2, 3-dicarboximide] (NRB, 1 ), an existing but infrequently used rodenticide, is known to be uniquely toxic to rats, but relatively harmless to other rodents and mammals. As a vasoactive agent, NRB induces a species-specific vasocontractile effect that is restricted to the peripheral arteries of the rat. Despite the precise mechanisms behind this phenomenon having yet to be fully clarified, it is postulated that the molecular target of NRB could be located within the plasma membrane of rat peripheral artery myocytes (e.g. rat caudal artery myocytes). As such, the primary objective of this study was to develop a fluorescently labelled derivative of NRB to investigate its subcellular distribution/localization in both NRB-sensitive (freshly isolated rat caudal artery myocytes, FIRCAMs) and NRB-insensitive (human hepatic stellate, LX2) cells. Of the examples prepared, lead structure endo -NRB-NBD- b PA subsequently demonstrated retention of the parent toxicant's pharmacological profile (in terms of its ability to induce both a vasocontractile response in rat caudal artery rings in vitro, and a lethal end-point in rats in vivo ). Endo -NRB-NBD- b PA was also shown to be significantly less permeable (an integral feature in the design of fluorescent probes targeting cell-surface receptors) to both LX2 cells and FIRCAMs. Disappointingly, no fluorescence could be observed on the plasma membrane of FIRCAMs stained with endo -NRB-NBD- b PA.